SEKURITISASI ISU IDENTITAS PADA PERANG NAGORNO-KARABAKAH TAHUN 2020 - Irsadi, Adib; Fahriansyah, Ori; Nge, Herri Junius (Department of International Relations Universitas Pertamina, 2022)
The conflict between Azerbaijan and Armenia has persisted for over a century, primarily revolving around cultural issues and territorial disputes, particularly concerning Nagorno-Karabakh. Since the first Nagorno-Karabakh war (1994), the two countries have been in conflict at least seven times, varying in intensity. The conflicts in 1994 and 2020 were the two largest in the history of both countries. This research is a descriptive study with a qualitative approach, aiming to explain the securitization process undertaken by Azerbaijan in the 2020 Nagorno-Karabakh War. The study employs the Copenhagen School's securitization theory based on Barry Buzan’s “Security: A New Framework for Analysis”. The research concludes that the modern Azerbaijan identity is significantly influenced by the Nagorno-Karabakh issue and anti-Armenian sentiments. These sentiments facilitate the Azerbaijani government in securitizing Nagorno-Karabakh issue as an existential threat to the identity of Azerbaijan. The securitization process by the Azerbaijani government involves the education system and mass media in shaping national identity.